Pencegahan Pasien ISPA pada Layanan Primer dengan Pendekatan Kedokteran Keluarga - Hendra Kurniawan; Syahrizal, Syahrizal; Qaid Alfayyad Haris; Muhammad Haykal Aulia; Nisa Salsabila (Yayasan Literasi Sains Indonesia, 2025)
Acute Respiratory Infection (ARI) is one of the most common diseases encountered in primary healthcare services and can be caused by various microorganisms such as viruses, bacteria, and fungi. This study aims to evaluate the implementation of home visits in the management of ARI patients at Primary Health Center Batoh. The methods used include two home visits with a six-day interval, anamnesis, physical examination, and completion of a family folder consisting of a family genogram, family map, and family function evaluation using APGAR and SCREEM. The first home visit was conducted to collect basic patient data, provide health education, and identify risk factors in the home environment. The second visit evaluated patient adherence to therapy and changes in clinical conditions.The results of the study indicate that home visits help in monitoring patient conditions, providing more effective health education, and increasing family involvement in patient care. Additionally, home visits enable healthcare providers to identify risk factors in the home environment that may worsen the patient’s condition, such as smoking habits and poor sanitation.The discussion in this study highlights that a holistic approach through home visits can improve treatment effectiveness and patient adherence to medication. In conclusion, the home visit program has proven to be an effective strategy in managing ARI in primary healthcare services and has the potential to improve the quality of life of patients and their families. Enhancing the implementation of this program is expected to become an integral part of family medicine approaches in primary healthcare facilities.